Analysis of Family Food Consumption Behavior (Case Study: Beneficiaries of Government Food Reserve Rice in Palopo City) - Hadisah, Lilis; Dewi Marwati Nuryanti; Idawati Idawati; Burhanuddin Harahap (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Study analyzes the behavior of food consumption patterns of families benefiting from the Government Food Reserve Rice (CPP) in Palopo City with a quantitative descriptive approach. Primary data was obtained through a multiple-pass 24-hour food recall survey of 115 beneficiary families spread across three agroecological characteristics: agriculture, fisheries, and others. Food consumption was analyzed based on nine food groups according to the Expected Food Pattern (PPH), concerning the national Nutritional Adequacy Rate (AKG). The results showed that grains, especially milled rice, became the dominant source of food and energy throughout the region, contributing an average of 1644.5 kcal/capita/day, or about two-thirds of total daily energy. Consumption of animal food, especially fish, is relatively high in agricultural and fishery areas, but its contribution to protein fulfillment is not optimal. Consumption of vegetables is considerable in volume but low in energy contribution and does not yet meet the WHO recommendations of â‰¥400 g/day. The average Energy Adequacy Level (TKE) is 78.3% of AKE, below the Minimum Service Standard of 90%, indicating food insecurity. Analysis between regions shows that agricultural areas have the highest energy intake, while other regions have the lowest. These results indicate a gap in food access, high dependence on a single carbohydrate source, and low food diversification. This study recommends interventions in the form of increasing access to and consumption of animal and vegetable proteins, diversifying carbohydrate sources, and nutrition education based on local wisdom to support sustainable food security among CPP beneficiaries.